Methodological strategies of teaching-learning to develop communicative skills in english as a foreign language with children of 3rd year of basic education at “Victor Emilio Valdivieso” neighborhood school period 2010-2011 - Carrion Fernández, Andrea Sthefania (2012)
The present research work entitled: methodological strategies of teaching-learning to develop communicative skills in English as a foreign language with children of 3rd year of basic education at “Victor Emilio Valdivieso” neighborhood, school period 2010-2011, has as purpose to develop methodological strategies during the teaching learning process. The methods applied were audio lingual, total physical response, communicative language teaching, direct, and notional functional. The strategies applied were role-plays, songs, games etc; besides the instrument applied was a diagnostic test; and for planning the English classes was used an annual plan, unit plans and lesson plans; through them it was possible to develop the communicative skills of English as a foreign language. The principal results that I found during the community program intervention was that the applied methodological strategies helped to develop the communicative skills in children during the teaching-learning process, which is evident in the children since they began to use the foreign language in a satisfactory level.